Efficient and Stable CsPbI3 Solar Cells via Regulating Lattice Distortion with Surface Organic Terminal Groups. Issue 24 (18th April 2019) - Wu, Tianhao; Wang, Yanbo; Dai, Zhensheng; Cui, Danyu; Wang, Tao; Meng, Xiangyue; Bi, Enbing; Yang, Xudong; Han, Liyuan
Abstract: All‐inorganic cesium lead iodide perovskites (CsPbI3 ) are promising wide‐bandgap materials for use in the perovskite/silicon tandem solar cells, but they easily undergo a phase transition from a cubic black phase to an orthorhombic yellow phase under ambient conditions. It is shown that this phase transition is triggered by moisture that causes distortion of the corner‐sharing octahedral framework ([PbI6 ] 4− ). Here, a novel strategy to suppress the octahedral tilting of [PbI6 ] 4− units in cubic CsPbI3 by systematically controlling the steric hindrance of surface organic terminal groups is provided. This steric hindrance effectively prevents the lattice distortion and thus increases the energy barrier for phase transition. This mechanism is verified by X‐ray diffraction measurements and density functional theory calculations. Meanwhile, the formation of an organic capping layer can also passivate the surface electronic trap states of perovskite absorber. These modifications contribute to a stable power conversion efficiency (PCE) of 13.2% for the inverted planar perovskite solar cells (PSCs), which is the highest efficiency achieved by the inverted‐structure inorganic PSCs. More importantly, the optimized devices retained 85% of their initial PCE after aging under ambient conditions for 30 days. Abstract : A novel strategy for achieving efficient and stable CsPbI3 solar cells via regulating lattice distortion with a surface organic terminal group (OTG) is proposed. As the steric hindrance of the OTG increases, the CsPbI3 perovskite will be more stable under ambient conditions. Consequently, the optimized CsPbI3 device shows negligible degradation of efficiency after 30 day aging in ambient air.